Physicochemical Properties of Fresh and Dry Powder Bekasam of Catfish Clarias batrachus (Linn, 1758): Bekasam Physicochemical Properties - Lestari, Yanesti Nuravianda; Murwani, Retno; Agustini, Tri Winarni (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
Bekasam, a fermented fish product with high salt content and strong specific flavor, can be used as a flavor enhancer to stimulate appetite. It is traditionally made either of skipjack viscera or whole fish or from various types of fish. The aim of this study was to characterize the physicochemical properties of fresh bekasam and bekasam powder made of catfish [Clarias batrachus (Linn, 1758)]. Fresh catfish free of viscera and head were fermented in the presence of 10 % salt for 24 h at room temperature followed by addition of glutinous rice and fermented further for 6 d. The resulting bekasam was partly dried by cabinet drier to produce bekasam powder. The pH, organic acid, soluble protein, sodium, and glutamic acid content of fresh bekasam and bekasam powder were measured. Fresh bekasam has pH value of pH 6.95 ± 0.010; organic acid (8.40 ± 0.040) %; soluble protein (1.59 ± 0.006) mg ∙ dL–1; sodium content (4.67 ± 0.006) %; and glutamic acid (11.88 ± 0.025) mg ∙ g–1. Bekasam powder has lower pH, organic acid, and glutamic acid but higher soluble protein and sodium than fresh bekasam. The dry powder had lighter brown color and specific bekasam odor with less intensity which is physically better than fresh bekasam. Dry catfish bekasam powder therefore can serve as flavor enhancer. Specific bekasam odor with less intensity which is physically better than fresh bekasam. Dry catfish bekasam powder therefore can serve as flavor enhancer.